COMMUNICATIVE - CREATIVE ABILITIES AS PGNPKNY INDICATOR OF COMMUNICATIVE TEACHER CULTURES - О.А. Havrylyuk (Academy of Cognitive and Natural Sciences, 2000)
The article describes communicative and creative abilities as the features of teachers' communicative culture. The author gives the structure and the definition of communicative abilities and the ways of their development and formation.